PELATIHAN DIGITAL ENTREPRENEURSHIP DALAM MENANAMKAN NILAI-NILAI PANCASILA BAGI MAHASISWA - Anna Marganingsih; Mardawani Mardawani; Emilia Dewiwati Pelipa; Eliana Yunitha Seran (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
Currently, the development of digital technology has brought significant changes in various aspects of life, including the world of education and entrepreneurship. Students are required to have comprehensive academic abilities and the ability to utilize digital technology in developing an entrepreneurial spirit based on Pancasila values. But on the other hand, the development of the digital world can also bring new challenges such as the emergence of business practices that lack regard for ethics, social responsibility, honesty and human values. Therefore, the devotees see the need for coaching efforts through community service activities regarding digital entrepreneurship based on Pancasila values which aim to improve student understanding. This service was carried out at the Economic Education Study Program of STKIP Persada Khatulistiwa Sintang with the participation of 25 students in the fourth semester. The method used is the lecture method with question and answer sessions and interactive discussions. The results of the activity showed that the students participating in the training had high enthusiasm. Participants gained a better understanding of the importance of developing digital-based businesses without leaving the values of Pancasila as the basis for carrying out economic activities. Students have an understanding that digital entrepreneurship is not only oriented towards economic profit, but must also prioritize honesty, responsibility, mutual cooperation, justice, and concern for the community.